Facilitators, barriers, and impacts to implementing dementia care training for staff in long-term care settings by using fully immersive virtual reality: a scoping review - Hung, Lillian; Ma, Carol Hok Ka; Huang, Chih Yun; Wong, Joey; Wong, Karen Lok Yi; Chew, Keng Hao; Chao, Ying Cheng; Hussein, Ali; Yuen, Katrina; Ren, Lily Haopu; Zhao, Yong (Frontiers in Virtual Reality, 2025)
BackgroundThe increasing ageing population highlights the urgent need for enhanced dementia care training among formal caregivers. Virtual reality technology has emerged as an innovative tool to address this challenge, offering potential improvements in training outcomes. This scoping review focuses on identifying the barriers, facilitators, and impacts of implementing fully immersive VR training programs for dementia care among staff in long-term care facilities.MethodThe Consolidated Framework for Implementation Research informed our searching strategies and data analysis. Following the Joanna Briggs Institute methodology and PRISMA-ScR guidelines, this review included both published and unpublished studies. A systematic search of CINAHL, MEDLINE, Embase, Scopus, Web of Science, and ProQuest databases yielded 469 publications, with nine articles meeting the inclusion criteria. These studies, published in English between 2015 and 2024, involved 362 formal caregivers with a mean age ranging from 44.7 to 65 years. VR interventions were found to foster empathy (through first-person perspectives) and to help participants recognize triggers of responsive behaviors and apply solutions (via second-person and third-person perspectives).ResultsMost barriers and facilitators were associated with the innovation domain. The primary barriers included simulation sickness, uncomfortable headsets, and limited immersive, interactive, and embodied experiences. Key facilitators were technical advantages, highly immersive, interactive, and embodied experiences, a safe training environment, individual attributes, and the provision of orientation and support during training. The VR training programs demonstrated the potential to impact caregiving at multiple levels, including initial reactions, learning (knowledge, skills, and attitudes), behavioral changes, and broader systemic outcomes.ConclusionThis scoping review maps out the current landscape of VR training for healthcare professionals. Future research should continuously improve the VR training experience by investigating the impact of VR training on dementia care outcomes, such as caregiver-resident interactions. By addressing the barriers and leveraging the facilitators, VR training can be successfully implemented to enhance the quality of care and wellbeing of residents living with dementia in long-term care homes.